IN-VITRO ANTI-OXIDANT ACTIVITY OF CITRULLUS LANATUS SEED - Rahman, Habibur; K, Manjula; T, Anoosha; K, Nagaveni; Eswaraiah, M. Chinna; Bardalai, Dipankar (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The objective of present work is to study the In-vitro anti-oxidant activities of n-Hexane, Chloroform and Ethanol extract of Citrullus lanatus seeds to find out the extract having highest anti-oxidant activity. Â Material and Methods: The In-vitro anti-oxidant activity of the extracts were studied using 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging activity, Ferric reducing power activity, Hyderogen peroxide(H2O2) scavenging activity and Nitric Oxide(NO) scavenging activity. The total Phenolic contents and Flavanoid contents were estimated taking Gallic Acid and Quercetin calibration curve respectably. Results: In In-vitro anti-oxidant studies it was found that all the extracts posses In-vitro anti-oxidant activities. But the order of possessing activities were n-hexane>ethanol>chloroform extracts of Citrullus lanatus seeds. The total Phenolic content was highest in n-hexane extract and Total Flavanoid content was highest in ethanol extract. Â Conclusion: It can be concluded that Citrullus lanatusseed extracts possess anti-oxidant activities and the potency of anti-oxidant activities depends on the type of extract. The n-hexane extract of Citrullus lanatus seeds possess highest anti-oxidant activity in-vitro. Keywords: Citrullus lanatus, In-vitro anti-oxidant, 1,1-diphenyl-2-picryl hydrazyl (DPPH), Total Phenolic Content,Â